Exploring the impact of triphenylmethane incorporation on physical properties of polyimides with emphasis on optical and halochromic behaviour. (18th June 2020) - Butnaru, Irina; Sava, Ion; Damaceanu, Mariana-Dana
Abstract: Three aromatic polyimides (PI) based on dimethyl-substituted 4, 4′-diaminotriphenylmethane (TPM) and three flexible aromatic dianhydrides with halochromic behaviour have been synthesized. The relationship between the architectural design of TPM-based PIs and their morphology, chain packing, thermal stability, mechanical properties, dielectric behaviour and molecular dynamics were analysed in detail. For the first time, we brought evidence for solute-polymer formation in TPM-based PI which arose from the interaction of unstable TPM carbocation forms with the polar solvent molecules. The thermal stability was high, with decomposition starting above 479°C, while good insulating properties are suggested by their dielectric constant values which ranged between 2.84 and 4.008. The optical and halochromic behaviour promoted by TPM core still unknown for this class of polymers were highlighted in correlation with the structural design. The TPM-based PI revealed solvent-solute interactions that generated strong absorptions in the visible range (596–599 nm) which were responsible for the unusual colour of these polyimides. The cyclic voltammetry data proved the ability of the polyimides to accept electrons and to behave as stable n -type materials. Graphical abstract: Image 1 Highlights: Dimethyl-substituted diaminotriphenylmethane (TPM)-based polyimides (PI) with halochromic behaviour have been synthesized. The evidence of solute-polymer formation in TPM-based PI was highlighted. Optical and electrochemical features for TPM-based PI were discussed for the first time.